2012
DOI: 10.1111/j.1468-1331.2012.03739.x
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease in unselected patients with TIA or stroke: population‐based study

Abstract: Fabry disease is rare in an unselected group of UK patients with TIA or stroke. Larger studies in unselected younger patients with cryptogenic stroke are required to determine whether routine screening is justified in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…The very low prevalence we found is consistent with most previous studies based on various designs (Table 4). [17][18][19][20][21][22][23][24][25][26][27] Two smaller North American studies 17,18 and most European studies [19][20][21][22][23][24] identified Fabry in 0.0% to 1.0% of cryptogenic IS or diverse other cerebrovascular conditions. Only 3 European studies reported a prevalence >1.0% in cryptogenic IS.…”
Section: Discussionmentioning
confidence: 99%
“…The very low prevalence we found is consistent with most previous studies based on various designs (Table 4). [17][18][19][20][21][22][23][24][25][26][27] Two smaller North American studies 17,18 and most European studies [19][20][21][22][23][24] identified Fabry in 0.0% to 1.0% of cryptogenic IS or diverse other cerebrovascular conditions. Only 3 European studies reported a prevalence >1.0% in cryptogenic IS.…”
Section: Discussionmentioning
confidence: 99%
“…Not only was it detected both in the BEFAS and the sifap study, but also in a recent study by Marquardt and colleagues. 18 Within a subcohort of the OXVASC study, 5 stroke patients with D313Y were detected. However, 3 of the 4 females identified were >90 years.…”
Section: Discussionmentioning
confidence: 99%
“…As the majority of these diseases resemble the MRI, digital subtraction angiography (DSA) and laboratory findings of angiitis, a biopsy of affected tissue is often necessary in order to prove the correct diagnosis. Moreover, detailed anamnesis and diagnostic work-up often allow diagnosis of non-inflammatory vasculopathies such as Moyamoya disease [47], Fabry's disease [48][49][50], Sneddon's syndrome [6] and RCVS [22,43,51,52]. For PACNS, a cerebral and meningeal biopsy is the gold standard for diagnosis.…”
Section: Diagnosis Of Definitive Vasculitismentioning
confidence: 99%